THE QUALITY OF CORN SILAGE PRODUCT FROM TECHNOPARK OF BANYUMULEK LOMBOK, WEST NUSA TENGGARA - Nurul Fitri Sari; Roni Ridwan; Yantyati Widyastuti (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
West Nusa Tenggara province is one potential area for farming of cattle and has been chosen as location for developing a Technopark in Banyumulek. Forage preservation as silage is a program to support the sustainability of forage for beef cattle. Silage was made using whole corn crop and additives of rice bran and Lactobacillus plantarum 1A-2 as inoculum under a block randomized design. Three treatments were given and 10 replications of each month. Evaluation of silage quality, based on chemical and microbiological analysis, showed that silage making during 3 months in Technopark Banyumulek is good and stable.